Successful SARS-CoV-2 mRNA Vaccination Program in Allogeneic Hematopoietic Stem Cell Transplant Recipients—A Retrospective Single-Center Analysis - Alexander Nikoloudis; Ines Julia Neumann; Veronika Buxhofer-Ausch; Sigrid Machherndl-Spandl; Michaela Binder; Emine Kaynak; Robert Milanov; Stefanie Nocker; Olga Stiefel; Irene Strassl; Dagmar Wipplinger; Margarete Moyses; et al. (Vaccines, 2023)
(1) Background: mRNA COVID-19 vaccines are effective but show varied efficacy in immunocompromised patients, including allogeneic hematopoietic stem cell transplant (HSCT) recipients. (2) Methods: A retrospective study on 167 HSCT recipients assessed humoral response to two mRNA vaccine doses, using the manufacturer cut-off of ≥7.1 BAU/mL, and examined factors affecting non-response. (3) Results: Twenty-two percent of HSCT recipients failed humoral response. Non-responders received the first vaccine a median of 10.2 (2.5–88.9) months post-HSCT versus 35.3 (3.0–215.0) months for responders (p < 0.001). Higher CD19 (B cell) counts favored vaccination response (adjusted odds ratio (aOR) 3.3 per 100 B-cells/microliters, p < 0.001), while ongoing mycophenolate mofetil (MMF) immunosuppression hindered it (aOR 0.04, p < 0.001). By multivariable analysis, the time from transplant to first vaccine did not remain a significant risk factor. A total of 92% of non-responders received a third mRNA dose, achieving additional 77% seroconversion. Non-converters mostly received a fourth dose, with an additional 50% success. Overall, a cumulative seroconversion rate of 93% was achieved after up to four doses. (4) Conclusion: mRNA vaccines are promising for HSCT recipients as early as 3 months post-HSCT. A majority seroconverted after four doses. MMF usage and low B cell counts are risk factors for non-response.